2023
DOI: 10.26803/ijlter.22.6.17
|View full text |Cite
|
Sign up to set email alerts
|

Gamification in Engineering Education during COVID-19: A Systematic Review on Design Considerations and Success Factors in its Implementation

Omar Chamorro-Atalaya,
Guillermo Morales-Romero,
Nicéforo Trinidad-Loli
et al.

Abstract: In pre-pandemic scenarios, various studies have indicated that gamification has turned out to contribute to improving student learning; however, in the context of the pandemic and in the face of the abrupt change to a virtual teaching modality, the need for learning innovations to overcome the limitations of social distancing was much more critical. Thus, this article aims to explore and describe the design considerations of gamification and the factors that evidenced its success in engineering education. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
1
0
1
Order By: Relevance
“…In terms of practicality, this research aligns with several prior studies that have also demonstrated a high level of practicality of mobilebased assessment for evaluating learning in higher education (Aguiar-Castillo et al, 2020;Chan et al, 2022;Sanchez et al, 2020). The findings of this study are consistent with earlier research, indicating that students perceive the use of this approach as an effective evaluation tool that is user-friendly and positively impacts their learning (Chamorro-Atalaya et al, 2023;Joshi et al, 2022;Kamaghe et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In terms of practicality, this research aligns with several prior studies that have also demonstrated a high level of practicality of mobilebased assessment for evaluating learning in higher education (Aguiar-Castillo et al, 2020;Chan et al, 2022;Sanchez et al, 2020). The findings of this study are consistent with earlier research, indicating that students perceive the use of this approach as an effective evaluation tool that is user-friendly and positively impacts their learning (Chamorro-Atalaya et al, 2023;Joshi et al, 2022;Kamaghe et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…Assessing student learning outcomes is an essential component of an effective learning process (Aguiar-Castillo et al, 2020;Chamorro-Atalaya et al, 2023;Díaz-Ramírez, 2020). In the context of the EMC, a comprehensive and accurate evaluation of students' comprehension of concepts and practical skills is crucial to ensure the achievement of learning objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Cuando se combina el constructivismo con la educación, el problema principal suele ser que se ha entendido que el enfoque permite a los alumnos aprender individualmente; sin que el docente intervenga en el proceso (Ortiz, 2015). En la actualidad, las tendencias y preocupaciones exigen que las generaciones jóvenes encuentren soluciones a sus expectativas tecnológicas y necesidades inmediatas en el ámbito educativo (Ortiz-Colón et al, 2018); a la vez es necesario construir normativas que regulen y promuevan la continuidad y sostenibilidad del uso de la gamificación (Chamorro-Atalaya et al, 2023). En la I.E., se evidencia en sus procesos internos una continuidad con el uso de las estrategias tradicionales de evaluación sumativa, el exceso de calificaciones negativas por no presentar ciertas actividades que requieren una elaboración fuera del centro educativo, incipiente uso del centro de cómputo, falta de capacitaciones integrales sobre avances en la forma de evaluar al estudiante y una ausencia del conocimiento tecnológico alineada a las TIC que generen cambios internos significativos en los procesos evaluativos.…”
Section: Introductionunclassified